Physical Fitness Factor Analysis on Employees at the Fertilizer Company - Rizka Dara Nabilah; Y. Denny Ardyanto (Universitas Airlangga, 2020)
Introduction: Work capacity is related to the ability required for finishing a job at a certain period, and its performance is influenced by physical fitness. PT Petrokimia Gresik's medical check-up result in 2018 showed that there were only 51% of employees with good physical fitness, 37.8% with average physical fitness, and the other 11.2% was not tested due to illness or was pregnant. The objective of this research was to understand the contributing factors that can affect the physical fitness of the employees that were actively involved in physical exercises in PT Petrokimia Gresik. Method: This research was non-reactive or unobtrusive with cross-sectional research design and conducted in December of 2019. The population was employees that have previously done medical check-up after physical exercise for more than 24 activities with a minimum of 126 km within 3 months amounted to 90 and had 55 samples gathered by using the simple random sampling technique. The independent variables were age, work period, and the frequency of exercise. The dependent variable was the physical fitness calculated by ergocycle during the medical check-up. The data analysis was done descriptively and the correlation test was done by the Chi-Square and Fisher’s Exact Test. Result: In this research, some employees were older than 30 years old (54.5%), male (98.2%), have working period longer than 3 years (65.6%), have normal-day working system (76.4%), performing exercises for at least 3x per week (56.4%), and had a good physical fitness (78.2%). Conclusion: age and working period are the factors related to the physical health of the employees, meanwhile exercising has no connection with the physical health of the employees if it is done without intensity and duration monitoring. Keywords: exercise, individual characteristics, physical fitness